Peran Proses Kognitif dalam Optimalisasi Pembelajaran: Kajian Teoritis dan Implementatif dalam Konteks Pendidikan Modern: The Role of Cognitive Processes in Optimizing Learning: Theoretical and Implementative Studies in the Context of Modern Education - Dzakhwanah Hanipah Ahmad (TARBIYAH: Jurnal Pendidikan dan Pembelajaran, 2025)
The cognitive process is the core of learning activities, determining how learners understand, process, and use information. Developments in cognitive theory within educational psychology have shifted learning paradigms from behavioristic approaches focused on observable responses to cognitive approaches that emphasize internal mental activities such as attention, perception, memory, reasoning, and problem-solving. In the context of modern education, learners are viewed as active information processors rather than passive recipients. This article provides a comprehensive discussion of the role of cognitive processes in learning by reviewing the theoretical foundations proposed by scholars such as Piaget, Vygotsky, Bruner, and Ausubel, and analyzing how metacognitive abilities contribute to academic success. In addition, this article highlights the challenges of the digital era, which requires learners to possess higher-order thinking skills to critically sort and evaluate information. The findings affirm that effective learning must be designed with an understanding of how the human mind works, through strategies such as chunking, elaboration, constructivism, problem-based learning, and self-regulated learning. Therefore, strengthening cognitive processes should be a priority in instructional design so that learners can adapt and contribute effectively within the complex and dynamic environment of the 21st century.